Yesterday and Today of Organic Farming in KOP Region - Havva Eda Üstüntaş; Ramazan İlhan Aytekin; Sevgi Çalışkan (Turkish Journal of Agriculture: Food Science and Technology)
Organic farming aims not to use chemical inputs, to increase quality not the yield, control and certify every steps of the production and is a human and environmental friendly production system. In recent years, use of organic food has increased parallel with the increasing interest in the environmental protection and safe foods in the developed countries. Turkey has a great potential for organic farming due to its wide diversity of climatic and soil conditions. KOP (Konya Plain Project) Region, includes the provinces as Aksaray, Karaman, Konya, Niğde, has a wide agricultural fields where not used chemical fertilizer and not contaminated with pesticides. Therefore this region is very important for organic agriculture. In 2013 year, planting area is 769.014 hectares and organic production is 1.620.466 tons in Turkey. KOP Region has a 0.47% planting area and 3.4% organic production in Turkey. Niğde which had the first rank in terms of organic production, constituted about 61% organic production amount. KOP Region could present significant opportunities and benefits to potential investors in terms of organic farming. In KOP Region, organic farming practices should be cared and supported.